Pengaruh Fee Audit dan Audit Tenure Terhadap Kualitas Audit pada Perusahaan Sub Sektor Basic Materials Yang Terdaftar di BEI 2020-2023 - Pertiwi, Dewi Asih; Hijriah, Amanah; Espa, Vitriyan (Forum Kerjasama Pendidikan Tinggi, 2024)
This research examines how the audit quality of companies in the basic materials sub sector, listed on the Indonesia Stock Exchange from 2020 to 2023, is affected by audit fees and audit tenure. This study uses a quantitative approach by involving a sample of 12 companies so that the total research data is 48. In addition, secondary data is used in this study, namely financial statements and annual reports. In this study, the analytical approach used is multiple linear regression. The results showed that audit fees have a significant positive effect on audit quality. Meanwhile, audit tenure has no effect on audit quality